Doubts about Normative Skepticism - Schueler, George F. (Journal of moral philosophy, 2025)
The ‘error theory’ holds that all normative claims are false. Of course, if there is any reason to believe the error theory then, since it would be a reason to believe something, that would show the error theory itself to be false. A recent book (Streumer, 2017) tries to block this argument by arguing on the basis of the claim that the error theory itself can’t be believed that there can be no reason to believe it. This is a paradoxical conclusion since it leaves the possibility that the error theory is true even though it is impossible to believe it and we can have no reason to believe it. In this paper I argue for a different paradox. Even if we can believe the error theory, we are committed to rejecting it, but this still leaves normative skepticism unanswered.